2013
DOI: 10.4187/respcare.01371
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ventilation Coupled With Nebulization During Asthma Crises: A Randomized Controlled Trial

Abstract: BACKGROUND: Despite the clinical improvements attributed to noninvasive ventilation (NIV) during asthma crises, and the well established effects of nebulization, there are few studies on the effects of these interventions together. We hypothesized that nebulization coupled to NIV should raise radio-aerosol pulmonary deposition in asthmatics. The aims of this study were to assess the effects of coupling ␤-agonist nebulization and NIV during asthma exacerbations on radio-aerosol pulmonary deposition, using scint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 29 publications
0
35
0
3
Order By: Relevance
“…156 Despite the impediments to efficient aerosol delivery with a bi-level ventilator, due to the continuous gas flow and leaks, substantial therapeutic effects are achieved after inhaled bronchodilator administration to patients with asthma and COPD. Galindo-Filho and colleagues 157 reported that, al-though coupling nebulization and NIV during an asthma exacerbation did not improve radio-aerosol pulmonary deposition, it did result in clinical improvement of pulmonary function in these patients. Careful attention to the technique of drug administration is required to optimize therapeutic effects of inhaled drugs during NIV.…”
Section: Can Inhaled Aerosols Be Delivered During Niv?mentioning
confidence: 94%
“…156 Despite the impediments to efficient aerosol delivery with a bi-level ventilator, due to the continuous gas flow and leaks, substantial therapeutic effects are achieved after inhaled bronchodilator administration to patients with asthma and COPD. Galindo-Filho and colleagues 157 reported that, al-though coupling nebulization and NIV during an asthma exacerbation did not improve radio-aerosol pulmonary deposition, it did result in clinical improvement of pulmonary function in these patients. Careful attention to the technique of drug administration is required to optimize therapeutic effects of inhaled drugs during NIV.…”
Section: Can Inhaled Aerosols Be Delivered During Niv?mentioning
confidence: 94%
“…The observation by Galindo-Filho et al 22 of an improvement in lung function without an increase in aerosol deposition during NIV suggests that there might be a bronchodilator effect of NIV unrelated to aerosol bronchodilator delivery. This is supported by the improvement in spirometry shown by Brandão et al 21 with a higher level of expiratory pressure.…”
Section: Asthmamentioning
confidence: 94%
“…Galindo-Filho et al 22 conducted a study to assess the effects of coupling ␤-agonist nebulization and NIV during asthma exacerbations. Specifically, they evaluated radioaerosol pulmonary deposition using scintigraphy and cardiopulmonary parameters to correlate pulmonary function with radioaerosol deposition index, radioaerosol penetration index, and pulmonary clearance.…”
Section: Asthmamentioning
confidence: 99%
“…The latest RCT was recently published in 2013, and the authors evaluated the effects of NIV on the pulmonary distribution of nebulized bronchodilators using pulmonary scintigraphy (20). Twenty-one patients who had presented to the ER with moderate-severe asthmatic attacks were randomized into two groups as follows: those receiving NIV and bronchodilator nebulization (10 patients) and the control group receiving nebulization without PS (11 patients).…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%